2019
DOI: 10.1057/s41599-019-0224-y
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive attraction and online misinformation

Abstract: The spread of online misinformation has gained mainstream attention in recent years. This paper approaches this phenomenon from a cultural evolution and cognitive anthropology perspective, focusing on the idea that some cultural traits can be successful because their content taps into general cognitive preferences. This research involves 260 articles from media outlets included in two authoritative lists of websites known for publishing hoaxes and 'fake news', tracking the presence of negative content, threat-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 35 publications
(34 reference statements)
4
66
1
Order By: Relevance
“…Recent research adopting this theoretical background to study digital media and online misinformation has proven fruitful (Acerbi, 2016(Acerbi, , 2019(Acerbi, , 2020. For example, Acerbi (2019) recently suggested that false information thrives not because it is lowquality information but due to its high psychological attractiveness. Being false per se does not increase the chances of information to become culturally successful, but having properties particularly appealing to the human mind does so (e.g.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research adopting this theoretical background to study digital media and online misinformation has proven fruitful (Acerbi, 2016(Acerbi, , 2019(Acerbi, , 2020. For example, Acerbi (2019) recently suggested that false information thrives not because it is lowquality information but due to its high psychological attractiveness. Being false per se does not increase the chances of information to become culturally successful, but having properties particularly appealing to the human mind does so (e.g.…”
mentioning
confidence: 99%
“…eliciting threat, disgust or related to social relations, see infra). Since false information is not constrained by reality, it can more easily be designed to recruit cognitive factors of attraction likely to appeal to the human mind and increase interactions (Acerbi, 2019). For example, in the current digital environment, information producers are encouraged to design clickbait-content with catchy titles to spur Internet users to react on them and to generate profit from their clicks.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This was not feasible in the design of the current study. Furthermore, elements of social media (e.g., anonymity) tend to lend themselves to "belligerent venting of anger" (Picard, 2015, p. 38) and individuals tend to be drawn to negative content (Acerbi, 2019). This may account for the high number of negative views/opinions (vs. positive content) that was noted in the collected data.…”
Section: Strengths and Limitationsmentioning
confidence: 99%